Prevention of Hospital-Acquired Venous Thromboembolism in Children: A Review of Published Guidelines - Faustino, E. Vincent S.; Raffini, Leslie J. (Frontiers in Pediatrics, 2017)
Venous thromboembolism, which includes deep venous thrombosis and pulmonary embolism, is a potentially preventable condition in children. In adults, pharmacologic prophylaxis has been shown to significantly reduce the incidence of venous thromboembolism in distinct patient cohorts. However, pediatric randomized controlled trials have failed to demonstrate the efficacy of pharmacologic prophylaxis against thrombosis associated with central venous catheters, the most important risk factor for venous thromboembolism in children. Despite the lack of supporting evidence, hospital-based initiatives are being undertaken to try to prevent venous thromboembolism in children. In this study, we sought to review the published guidelines on the prevention of venous thromboembolism in hospitalized children. We identified 5 guidelines, all of which were mainly targeted at adolescents and used various risk-stratification approaches. In low risk children, ambulation was the recommended prevention strategy, while mechanical prophylaxis was recommended for children at moderate risk and pharmacologic and mechanical prophylaxis were recommended for the high risk group. The effectiveness of these strategies has not been proven. In order to determine whether venous thromboembolism can be prevented in children, innovative clinical trial designs are needed. In the absence of these trials, guidelines can be a source of valuable information to inform our practice.